2000
DOI: 10.1126/science.287.5454.857
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of Marine Populations: Open or Closed?

Abstract: Most marine populations are thought to be well connected via long-distance dispersal of larval stages. Eulerian and Lagrangian flow models, coupled with linear mortality estimates, were used to examine this assumption. The findings show that when simple advection models are used, larval exchange rates may be overestimated; such simplistic models fail to account for a decrease of up to nine orders of magnitude in larval concentrations resulting from diffusion and mortality. The alternative process of larval ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
848
3
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,022 publications
(907 citation statements)
references
References 32 publications
30
848
3
11
Order By: Relevance
“…duration of larval life), suitable habitat and the features of the transient habitats (e.g. ocean currents; Gosline, 1955;Cowen et al, 2000;White et al, 2010). This is particularly important in some bentho-pelagic species where the adults are highly sedentary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…duration of larval life), suitable habitat and the features of the transient habitats (e.g. ocean currents; Gosline, 1955;Cowen et al, 2000;White et al, 2010). This is particularly important in some bentho-pelagic species where the adults are highly sedentary.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important in some bentho-pelagic species where the adults are highly sedentary. Oceanographic features such as ocean currents, upwelling zones and eddies maintain or prevent connectivity over periods of time (Cowen et al, 2000). However, long distance sporadic dispersal is also possible through various mechanisms in the marine environment.…”
Section: Introductionmentioning
confidence: 99%
“…Early life history is determinant in a species' ecology since it has profound implications in demography, dispersal and population connectivity (Cowen et al, 2000;Armsworth, 2002). Species with a pelagic early life stage have, at least theoretically, the capacity to colonize new areas and/or promote gene £ow between geographically separated populations, by drifting on water currents.…”
Section: For This Species]mentioning
confidence: 99%
“…In this stage, extensive exchange of genetic resources and substantial new recruitment from other regions are possible (Caley et al 1996). Recently, however, it was found that even in the case of species that have the ability for long-range dispersal, recruitment occurs close to the natal place, especially in coral reef fish species (Jones et al 1999, Cowen et al 2000, Taylor & Hellberg 2003; reviewed in Levin 2006, Jones et al 2009). Self-recruitment has also been reported in reef corals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…short-range dispersal) or broadcasting. Long-range dispersal increases the chances of reaching new unoccupied habitats; nevertheless, larval behaviors and the risk of diffusion and mortality during migration may reduce the feasible range of dispersal from the natal reef (Cowen et al 2000). Although the major role of larval behaviors in the pelagic phase is still unknown, a laboratory experiment demonstrated that coral larvae placed in seawater collected directly above a shallow reef swam downward and began benthic probing, whereas such behavior was uncommon for larvae placed in seawater collected offshore (> 50 m depth) (Gleason et al 2009).…”
Section: Introductionmentioning
confidence: 99%